POWER, KNOWLEDGE, AND CENSORSHIP IN 19TH-CENTURY RUSSIA - Igor M. Chubarov (Высшее образование в России, 2022)
The core idea of this article is to investigate a connection between clerical and secular censorship and the development of Russian philosophy, literature and journalism in XIXth century. Censorship became a despositive of paradoxical social congruence on questions of individuality, discourse, Truth and coercion in Russian society. Quite a compatible situation was raised in the works on sexuality by Foucault. Thus, the main goal of this article is to make a comparative study of papers related to Russian prison and censorship and Foucault methods.